Recruit fitness as a predictor of police academy graduation - Shusko, M.; Benedetti, L.; Korre, Maria; Eshleman, Emily J.; Farioli, Andrea; Christophi, Costas A.; Kales, Stefanos N. (My University, 2017)
Background: Suboptimal recruit fitness may be a risk factor for poor performance, injury, illness, and lost time during police academy training. Aims: To assess the probability of successful completion and graduation from a police academy as a function of recruits' baseline fitness levels at the time of academy entry. Methods: Retrospective study where all available records from recruit training courses held (2006-2012) at all Massachusetts municipal police academies were reviewed and analysed. Entry fitness levels were quantified from the following measures, as recorded at the start of each training class: body composition, push-ups, sit-ups, sit-and-reach, and 1.5-mile run-time. The primary outcome of interest was the odds of not successfully graduating from an academy. We used generalized linear mixed models in order to fit logistic regression models with random intercepts for assessing the probability of not graduating, based on entry-level fitness. The primary analyses were restricted to recruits with complete entry-level fitness data. Results: The fitness measures most strongly associated with academy failure were lesser number of pushups completed (odds ratio [OR] = 5.2, 95% confidence interval [CI] 2.3-11.7, for 20 versus 41-60 push-ups) and slower run times (OR = 3.8, 95% CI 1.8-7.8, [1.5 mile run time of ≥ 15'20"] versus [12'33" to 10'37"]). Conclusions: Baseline pushups and 1.5-mile run-time showed the best ability to predict successful academy graduation, especially when considered together. Future research should include prospective validation of entry-level fitness as a predictor of subsequent police academy success.
Keywords: Aerobic; Cooper Fitness; Police; Push-up; Recruits; VO2 max